Functional materials in desalination: A review - Nidal Hilal (Desalination, 2019)
This paper reviews various functional materials used in desalination. Desalination of the abundant seawater resource has emerged as a promising technology to meet the current fresh water demands. For improved performance, often functional materials such as photocatalysts, electrocatalysts, photothermal materials, sorbents, antibacterial materials and magnetic materials are utilized in thermal, membrane-based and other desalination technologies. With an aim to provide an insight on the existing research on functional materials and the purpose behind using such in desalination, this review collates different research studies of various functional properties and the subsequent materials utilized for those properties. New generation materials such as carbon nanotubes (CNTs) and graphene form a major part, where they exhibit multiple functionalities with improved water transport properties, and thus have been deemed as very attractive enhancers to the desalination technology. Nevertheless, most of the functional materials, such as nano-TiO2, nano-zeolites, graphene, CNTs and magnetic nanoparticles suffer from several limitations such as specialized synthesis techniques, agglomeration, leaching and environmental and health concerns. This review focuses on such challenges and suggests improvements for enhanced incorporation of these in the desalination technology. Lastly, emerging new technologies, advanced fabrication methods and novel functional hybrid materials are reviewed to equip the readers with the latest research trends. Thus, a comprehensive review is essential which will provide current and future researchers an insight on the importance and significance of utilizing functional materials in various desalination technologies.